Report on professional attachment with Civil Aviation Authority of Singapore. - Toh, Chiang Ling. (2009)
This report will be a summary of my work nature and experience gained throughout the two months professional attachment with CAAS internal audit division. The first two chapters of the report will be an introduction on both CAAS and the Internal Audit Division. My attachment with the department provides opportunities for me to work on various assignments. They include revenue audit, test-buy, physical stocktake, observation on performance of cleaning service contract and updating data into the computer system. The other chapters of the report will concentrate on description of my work assignment and recommendations that can improve the efficiency of the present system.